The border as a space of exchange in the 18th century - Botica, Dubravka (Acta historiae artis Slovenica, 2025)
In Central Europe, borders are not solid barriers but are rather fluid. Central Europe is a deeply connected cultural space of intensive exchange (M. Csáky) in which artistic production is shaped by densely intertwined mutual contacts and influences between individual countries and regions. This is particularly visible in the activities of large architec-tural, painting and sculptural workshops in the 18th century, which had a wide network of collaborators throughout the area. A key role in the rapid and far-reaching transfer of artistic solutions was played by the commissioners of artworks, both ecclesiastical and secular, strongly connected by a dense network of contacts that did not stop at (today’s national) borders. This paper studies the example of the activities of the architectural workshop of Joseph Hueber from Graz (1715–1787) in historical Styria, present-day Austria, and Lower Styria (present-day Slovenia) and northwestern Croatia to explore the method and scope of the workshop’s work, as well as the reconstruction of contacts between commissioners from the ranks of the Styrian, Hungarian and Croatian nobility.
Keywords: architects; architecture; arhitekti; art patronage; baročna arhitektura; Baroque architecture; borders; building workshops; Hueber, Joseph; meje; nobility; plemstvo; stavbarske delavnice; umetnostno naročništvo